FREEDOM AND CHOICE IN HUMAN RELATIONSHIPS IN SIMONE DE BEAUVOIR’S SELECTED NOVELS (2016)
Freedom and choice are among the most fundamental ethics in Existentialism that have generated extensive research in French literature. Past studies concentrated on the works of French existentialist writers in the areas of freedom and choice in politics, religion, education and the meaning of human existence with little attention paid to writers like Simone de Beauvoir who focuses on freedom in human sexuality. This study, therefore, examined sexuality in human relationships in selected texts of Simone de Beauvoir with a view to portraying the author’s core existentialist principles of freedom and choice. The study adopted Existentialism and Radical Feminism as framework. Four novels of Simone de Beauvoir namely: L’invitée, Le sang des autres, Les mandarins and Les belles images, were purposively selected because they dwell on human relationships, and expose characters’ exercise of existential freedom in their sexual relationships. The texts were analysed using “explication de texte.” Relationships portrayed within the texts include heterosexual, homosexual and bisexual, both in marital and extra-marital associations. The writer’s ethics of freedom and choice within the context of love and passion are manifested differently in characters and situations. Characters that enjoyed true existential freedom are those who lived “authentic life,” which gives the individual the opportunity to be himself in freedom and responsibility. Les mandarins and Les belles images demonstrated “authenticity” in heterosexual relationships through Lucie, Lucile, Josette and Nadine who exploited their sexuality to free themselves from unwanted and difficult circumstances. Other characters that enjoyed true existential freedom in their sexual relationships without societal constraints included Jean and Hélène in Le sang des autres, Robert, Anne, Lewis and Henri in Les mandarins. These characters rejected societal values that restrain their capacity to choose by having relationships with multiple sexual partners. However, when characters resorted to “inauthentic life,” they denied their freedom and allowed the “Other” to choose for them. “Inauthentic life” suppressed the freedom of the individual by imposing uniformity or norm and often results in oppression and exploitation. Exploitation is one-sided in some relationships while it is mutual in others. Henri was the exploiter in his relationship with Paule, while he exploited and was also exploited by Josette. L’invitée, Les belles images and Le sang des autres portrayed that choice is consequential and could lead to the suffering of the “self.” This is illustrated in the case of Laurence and Lucien who both suffered when their sexual relationship broke up due to pressures from the “Other.” Exploitation is part of human relationship; true existential freedom can only be enjoyed when there is “authentic” life. From the view point of Simone de Beauvoir, therefore, individuals must reject “inauthenticity” by owning up and readily accepting responsibility for their freedom.